Dimensional analysis and CFD simulations of microcarrier 'just-suspended' state in mesenchymal stromal cells bioreactors. (10th August 2019) - Loubière, C.; Delafosse, A.; Guedon, E.; Chevalot, I.; Toye, D.; Olmos, E.
Highlights: Zwietering's model is revisited in the case of microcarrier suspension. Njs was better predicted using dimensional analysis proposed model. CFD simulations of microcarrier Njs were validated. Dimensionless number of particles should be preferred to d p / D ratio. Impact of particle concentration on Njs was dependent on flow structures. Abstract: Large-scale mesenchymal stem/stromal cells culture uses 3D culture systems involving spherical solid particles, called microcarriers. Cells adhere on these spheres, which are then set in suspension in stirred tank bioreactors. This work was more particularly focused on the determination of the critical impeller agitation rate N js, allowing complete beads suspension. It is indeed generally assumed that this value is a good compromise between sufficient nutrients homogenization, mass transfer and minimization of hydromechanical stress encountered by the cells. However, no robust correlation predicting N js in the case of microcarriers can be found in literature. To fill this lack, a set of various operating conditions was carried out, dealing with geometrical variables and two different microcarriers, and N js were experimentally determined for 140 conditions. An empirical correlation was established and a dimensional analysis was performed, showing that the impact of the particle concentration on N js was function of the impeller design. Moreover, two dimensionless numbers characterizing the number of particle and an Archimede number applied on the particle cloud were found to better describe the impact of particle diameter and density on N js . Simultaneously, a strategy based on Computational Fluid Dynamics simulations was conducted in order to predict N js and was validated with the N js experimental values.